Draft Proposal for a National Center for Computational Chemistry at the Los Alamos Scientific Laboratory of the University of California - Los Alamos National Laboratory (1974)
Preliminary draft, prepared by staff of the Los Alamos Scientific Laboratory, of a proposal for the University of California to operate the National Center for Computational Chemistry at the Los Alamos Scientific Laboratory.
Keywords: University of California, Berkeley; Computational chemistry; Los Alamos National Laboratory; National Science Foundation (U.S.)